Kebijakan Pemerintah Kabupaten Pati dalam Penataan Tempat Hiburan Karaoke - Putri, Devi Tantia; Handoyo, Eko; Ngabiyanto, Ngabiyanto (Unnes Political Science Journal, 2018)
Policy is a course of action that has the meaning assigned by an actor or actors in overcoming a problem that was chosen by the government to do and not do. Policy in this case is the inventor of karaoke entertainment in Pati plaguing the society. The problems in this research are:  How is the governments policy in the arrangement Pati karaoke entertainment, How can businesses and communities in response to settlement of karaoke entertainment. The method used is qualitative research. The research location is in Pati regency. The data used are primary data and secondary data. Mechanical collecting data were interviews, observation and documentation. Analysis of the data in this study using an interactive analysis of Miles and Huberman.Results showed that: the governments policy on the restructuring Pati regency karaoke entertainment venues have been formulated by Regulations No. 8 of 2013 on the implementation of Tourism in the regulation governing the arrangement of places within the location with the citizens, the arrangement permits karaoke, structuring the operational time, the arrangement of visitors karaoke, business response karaoke reject their governments policy of district Pati on the restructuring of a karaoke among which, employees karaoke, guides karaoke, but the response of the community that supports the government policy Pati regency in structuring a karaoke diataranya ie, the surrounding community, students, organizations NU, officials Police / law, schools, housewives, one who refused that visitors karaoke. suggestion the proposed research are as follows: To the government, the government should increase and maximize the implementation Regulation No. 8 of 2013 on the restructuring of karaoke entertainment venues in Pati regency. To the entrepreneur, to implement and set up a karaoke entertainment in accordance with the government policy set out in Regulation No. 8 of 2013 on the implementation of Tourism. To society, people should be more concerned about the karaoke entertainment venues in the environment if it is felt there is a veiled karaoke can directly report. Provide support by reporting karaoke violate the law to support government efforts in structuring karaoke entertainment.